Geochemical Characteristics of Sediment in Tropical Lake Sentani, Indonesia, Are Influenced by Spatial Differences in Catchment Geology and Water Column Stratification - Nomosatryo, Sulung; Tjallingii, Rik; Schleicher, Anja Maria; Boli, Paulus; Henny, Cynthia; Wagner, Dirk; Kallmeyer, Jens (Frontiers in Earth Science, 2021)
Physical and (bio)chemical processes in the catchment as well as internal lake processes influence the composition of lacustrine sediments. Lake internal processes are a consequence of reactions and fluxes between sediment, porewater and the water column. Due to its separation into four interconnected sub-basins, Lake Sentani, West Papua Province, Indonesia, is a unique tropical lake that reveals a wide range of geochemical conditions. The highly diverse geological catchment causes mineralogical and chemical differentiation of the sediment input into each sub-basin. Also, strong morphological differences between the sub-basins result in a unique water column structure for each sub-basin, ranging from fully mixed to meromictic. Given the strong differences in sediment composition and bottom water chemistry among the four sub-basins, Lake Sentani offers a unique chance to study multiple lacustrine systems under identical climate conditions and with a common surface water chemistry. We used sediment cores and water samples and measured physicochemical water column profiles to reveal the geochemical characteristics of the water column, the sediment and pore water for all four sub-basins of Lake Sentani. The chemical composition of the sediment reveals differentiation among the sub-basins according to their sediment input and water column structure. Catchment lithology mainly affects overall sediment composition, whereas pore water chemistry is also affected by water column structure, which is related to basin morphology and water depth. In the meromictic sub-basins the bottom water and sediment pore water appear to form a single continuous system, whereas in those sub-basins with oxygenated bottom water the sediment-water interface forms a pronounced chemical barrier.